عوامل العنف الأسري وعلاقته بنشوء السلوك العدواني لدى الأبناء دراسة ميدانية على عينة من طلاب مرحلة التعليم الأساسي (حلقة ثانية) في محافظة طرطوس - Tayoub, Mahmoud; Bashmani, Shakib; Hasan, Mouna (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى الكشف عن العلاقة بين العنف الأسري تجاه الأبناء ونشوء السلوك العدواني لديهم في مدارسهم من خلال عدة متغيرات: العلاقة بين الوالدين, المستوى التعليمي للوالدين, المستوى الاقتصادي للأسرة. ولتحقيق أغراض البحث قامت الباحثة بتصميم أداة الدراسة (استبانة) وتطبيقها على عينة مختارة عشوائياً مؤلفة من 120 طالباً وانتهى البحث إلى النتائج الآتية: 1- وجود علاقة موجبة ذات دلالة إحصائية بين العنف الأسري ونشوء السلوك العدواني لدى الأبناء. 2- وجود علاقة سالبة ذات دلالة إحصائية بين المستوى التعليمي للوالدين والعنف الأسري. 3- وجود علاقة سالبة ذات دلالة إحصائية بين المستوى الاقتصادي للأسرة والعنف الأسري. The research aims to show the relation between familial violence towards children, and the emergence of their aggressive behavior in their schools via many variables: the relation between parents, their educational level, the economic level of the family. To achieve this, the researcher designed the study tool (questionnaire) , and applied it to a randomly chosen sample of 120 students. The research concluded the following results: 1- Positive relation of statistical significance between the familial violence and the emergence of the aggressive behavior in children. 2- Negative relation of statistical significance between the educational level of the parents and the familial violence. 3- Negative relation of statistical significance between the economic level of the family and the familial violence.